(untitled) (The Research of Medical Science Review, 2025)
AIDS and HIV positive patients require specialized healthcare facilitation due to nature of the disease and its social, cultural and contextual concerns amongst the society. As a result, the existing facilities with respect to the higher influx of patients are too short to meet the needs as well as fulfilling the medical. Mental. Psychological and social needs. Hence there was a need to explore the existing trauma of patients due to poor or negligible healthcare infrastructure to support them. The research explored the avenue with an objective to bridge the gap between the patients and the system towards enabling and developing consensus towards future needs and direction of healthcare facilities design to manage the burden of disease. Qualitative research methodology using questionnaires from three different patients with diversified sources of infection were contacted and explorative means were used to collect data from allied medical teams and later were analyzed with respect to design and spatial requirements baselining for such facilities. It was concluded that there were major gaps in design of such facilities apart from lack of mere existence as well as lack of understanding of the multifold psychological mental, physiological and social needs of the patients which require design interventions to help develop better solutions to these pivotal issues.